Applied Bibliometric in the Advancement of Solar Energy Research (2022)
existing data and documents to resolve trends in specific research fields. Considering the database downloaded from Web of Science, with the help of Hitscite and VOSviewer data analysis tool and Microsoft Excel table, 7,259 publications related to solar energy research from 2010 to 2020 were obtained. The purpose of this research work is to apply bibliometric analysis methods to the development of scientific research on solar energy, as an important part of renewable energies, to evaluate its progress in the last decades and to describe these trends. The results showed that since 2015, research on solar energy has increased, especially in countries such as the United States and China, due to the Paris treaties where the goal is that the average temperature of the earth by the year 2100 does not exceed 1.5°C. Since greenhouse gases are the cause of the greatest impact of the increase in global temperature, it is expected that researchers will focus on harnessing green energy and take a step further to reduce fossil fuels.